The 4-hour chef : the simple path to cooking like a pro, learning anything, and living the good life - Ferriss, Timothy (New Harvest/Houghton Mifflin Harcourt ; produced by Melcher Media, 2012)
Building upon Timothy Ferriss's internationally successful "4-hour" franchise, "The 4-Hour Chef" transforms the way we cook, eat, and learn. Featuring recipes and cooking tricks from world-renowned chefs, and interspersed with the radically counterintuitive advice Ferriss's fans have come to expect, "The 4-Hour Chef" is a practical but unusual guide to mastering food and cooking, whether you are a seasoned pro or a blank-slate novice.